Strategi City Branding sebagai Daya Tarik Wisata Kuliner Kota Cirebon - Iva Yulia Mustafa; Agung Setiawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Cirebon City is recognized as one of the leading cultural and culinary tourism destinations in West Java, Indonesia, characterized by a rich variety of traditional foods that reflect its historical and cultural heritage. However, studies examining culinary tourism as a strategic instrument for city branding remain limited, as previous research has predominantly focused on destination marketing and tourism promotion in general. This study offers novelty by exploring the role of culinary tourism as a core component of Cirebon City's branding strategy through the dimensions of attributes, message, differentiation, and ambassadorship. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, documentation, and literature review. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that Cirebon’s iconic culinary products, such as Empal Gentong, Nasi Jamblang, Tahu Gejrot, and Docang, play a significant role in shaping a distinctive and authentic city identity that is easily recognized by tourists. The uniqueness of these culinary products, influenced by coastal, royal palace, and multicultural traditions, serves as a key differentiating factor that strengthens Cirebon’s position as a culinary tourism destination. Furthermore, positive culinary experiences foster emotional attachment among visitors, encourage revisit intentions, and stimulate positive word-of-mouth promotion. These findings indicate that culinary tourism represents a strategic asset for strengthening city branding and enhancing the sustainable competitiveness of Cirebon’s tourism sector.